2022
DOI: 10.1055/s-0037-1610794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclopropyl Pinacol Boronic Esters from Dibromo­cyclopropanes

Abstract: The synthesis of cyclopropyl pinacol boronic esters from dibromocyclopropanes via Matteson–Pasto rearrangement is reported. The method is readily scalable and shows limited levels of stereoinduction, with a selectivity that is in part complementary to that observed in existing stereoselective borylcyclopropanation strategies. The method can be used to rapidly access borylcyclopropanes as interesting building blocks for diversely functionalized cyclopropanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This approach has been recently revisited by the group of Neouchy, who published in 2022 the synthesis of stable cyclopropyl pinacol boronic esters 71 [32] . They demonstrated that the chelation of the lithium with an ether oxygen had unfortunately a limited effect on the reaction stereoselectivity (Scheme 15a), while the use of a fused 6‐membered ring 72 led to high level of diastereoselectivity (Scheme 15b).…”
Section: Strained Cycloalkanesmentioning
confidence: 99%
“…This approach has been recently revisited by the group of Neouchy, who published in 2022 the synthesis of stable cyclopropyl pinacol boronic esters 71 [32] . They demonstrated that the chelation of the lithium with an ether oxygen had unfortunately a limited effect on the reaction stereoselectivity (Scheme 15a), while the use of a fused 6‐membered ring 72 led to high level of diastereoselectivity (Scheme 15b).…”
Section: Strained Cycloalkanesmentioning
confidence: 99%